Emergent de Sitter epoch of the loop quantum cosmos: A detailed analysis - Assanioussi, Mehdi; Dapor, Andrea; Liegener, Klaus; Pawlowski, Tomasz (Physical Review D, 2019)
We present a detailed analysis of a quantum model for loop quantum cosmology based on strict application of the Thiemann regularization algorithm for the Hamiltonian in loop quantum gravity, extending the results presented previously in our brief report. This construction leads to a qualitative modification of the bounce paradigm. Quantum gravity effects still lead to a quantum bounce connecting deterministically large classical universes. However, the evolution features a large epoch of de Sitter Universe, with emergent cosmological constant of Planckian order, smoothly transiting into a spatially flat expanding universe. Moreover, we present an effective Hamiltonian describing the quantum evolution to high accuracy and for which the dynamics can be solved analytically.
CRIS-Team WoS Importer:2019-10-18